Beyond Rebellion: Uncaptured Dimensions of Violent Conflicts and the Implications for Peacebuilding in Nigeria's Niger Delta. Issue 1 (2nd January 2017) - Ebiede, Tarila Marclint
ABSTRACT: Disagreements between indigenous communities and the Nigerian state on natural resource management constitute a major source of conflicts in the oil-rich Niger Delta. Though armed militancy targeting oil infrastructure constituted a major form of the conflicts, there existed other types, levels, and dimensions of conflicts within the region. However, the Nigerian state response has focused mainly on addressing the armed militant conflict that targets oil industry infrastructure, leaving other—though connected—conflicts in the Niger Delta unattended. The neglect of other forms of conflicts, it is argued, impacts the ability of state-led peacebuilding programs to stabilize the Niger Delta region.